The Urgency of Legal Protection for Policyholders in Insurance Disputes in Indonesia - Nasywa Almira; Naya Salsabila; Lola Kesuma Pardosi; Syukur Hidayat Simatupang; Habib Hardimi Parhalim (ISNU Sumatera Utara, 2025)
Given the frequent occurrence of detrimental consumer conflicts such as claim rejections, late payments, and unclear policy interpretations, legal protection for insurance policyholders in Indonesia is a critical concern. The rights and obligations of the parties have been regulated in laws such as Law No. 40 of 2014 concerning Insurance and regulations of the Financial Services Authority (OJK), but their implementation and oversight still face significant challenges. This study uses a normative juridical method to investigate the obligations of insurance companies, the rights of policyholders, the roles of related organizations including the OJK, BPSK, and LAPS SJK in dispute resolution, and regulatory and implementation deficiencies in legal protection. The study's findings suggest that to provide efficient and fair legal protection, laws must be strengthened, consumer education must be expanded, and alternative dispute resolution procedures must be maximized. Therefore, strong legal protection can increase public trust in the insurance business and encourage its long-term expansion in Indonesia.